2021
DOI: 10.1115/1.4051709
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Stall Precursor Signatures

Abstract: A specific phenomenon that has been observed in many experimental studies on turbomachinery compressors and fans is discussed under the term ‘rotating instabilities’. It is associated to a local aerodynamic phenomenon, typically occurring in the tip region at highly loaded near stall conditions and often linked to blade vibrations. Even though the effect has been discussed over more than two decades, a very ambiguous interpretation still prevails. A particular problem is that certain signatures in measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…The paper has received a lot of attention, but it delivers few physical explanations regarding the nature of these disturbances or the mechanisms by which fluid and structure couple. (In the authors' opinion, the interpretation in this paper is misleading, and an interpretation of the measured data which is consistent with the latest understanding of NSV is possible [10]). Kielb et al [5] provided a physical explanation of NSV in the front stages of a compressor rig.…”
supporting
confidence: 57%
“…The paper has received a lot of attention, but it delivers few physical explanations regarding the nature of these disturbances or the mechanisms by which fluid and structure couple. (In the authors' opinion, the interpretation in this paper is misleading, and an interpretation of the measured data which is consistent with the latest understanding of NSV is possible [10]). Kielb et al [5] provided a physical explanation of NSV in the front stages of a compressor rig.…”
supporting
confidence: 57%
“…Within the mentioned broadband hump around EO 8, which is visible at OP DS4 in the WPT spectra of both configurations, distinct frequency peaks at EO 7.2 and EO 8.8 establish. These peaks indicate the presence of convective disturbances with nearly constant propagation speed in the stationary frame of reference, which is determined by the aerodynamics of the mean flow [33]. Rodrigues et al [28] have shown that it lies within 55 and 60 % of the rotational speed for the fan investigated here, what corresponds to a propagation velocity of…”
Section: Aeroelastic Behaviormentioning
confidence: 53%
“…The reduction in massflow from OP DS2 to OP DS4 results in rising noise levels and in the formation of a broadband hump around EO 8. This broadband hump denotes the presence of convective disturbances as described by Rodrigues et al [28] and Brandstetter et al [33].…”
Section: Unsteady Aerodynamicsmentioning
confidence: 67%
See 1 more Smart Citation
“…One frequently cited study of the topic links the excitation of structural vibration modes to socalled 'rotating instabilities', aerodynamic disturbances which propagate around the circumference, but offered few physical explanations regarding the physical mechanisms driving fluidstructure coupling [2]. The interpretation in this paper is misleading, and an interpretation of the measured data which is consistent with the latest understanding of NSV is possible [3]. Kielb et al [4] provided a physical explanation of 'nonsynchronous vibrations' in the front stages of a compressor rig, occurring at part-speed.…”
Section: Introductionmentioning
confidence: 82%